Freedom of Speech Boundaries in Criticizing Government on Social Media: Batasan Kebebasan Berekspresi dalam Mengkritik Pemerintah di Media Sosial - Hardiyati , Aisyah Dwi Putri; Multazam , M. Tanzil (Indonesian Journal of Public Policy Review, 2025)
General Background: Freedom of speech is a fundamental democratic right that enables citizens to express opinions, including criticism of government performance. Specific Background: However, in the digital era, especially on social media, this freedom often intersects with issues of defamation, raising legal and ethical challenges. Knowledge Gap: Previous studies have not sufficiently analyzed the boundary between legitimate criticism and defamatory statements within the context of online political discourse. Aims: This study aims to examine the balance between the right to freedom of expression and legal restrictions on defamation when evaluating government performance on social media. Results: The findings reveal that public expression is often constrained by ambiguous legal interpretations, causing fear of prosecution and limiting civic participation. Novelty: This research introduces a conceptual framework for distinguishing constructive criticism from defamation in digital political communication. Implications: The study emphasizes the need for clearer legal guidelines and public digital literacy to safeguard both individual rights and governmental integrity within online spaces. Highlights: Identifies boundaries between criticism and defamation online. Proposes a framework for fair digital political discourse. Recommends clearer regulations and public literacy efforts. Keywords: Freedom Of Speech, Defamation, Government Performance, Social Media, Public Policy